(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2019)
The article provides the analisys of the victmis alowance as an element of the legal description of the felony of human traffi c, and the current importance of considering the victim´s vulnerability situation to characterize it, due to the changes operated in time in Brazilian criminal law.